Pregnant and active – suitability of the Pregnancy Physical Activity Questionnaire for measuring the physical activity of pregnant women in Poland - Justyna Krzepota; Dorota Sadowska (Family Medicine & Primary Care Review, 2017)
Background . The issue of physical activity of pregnant women, including determining proper recommendations, has been a broadly discussed topic in international circles. Objectives. The aim of this paper is to present the suitability of the Pregnancy Physical Activity Questionnaire (PPAQ) for measuring the physical activity of pregnant women in Poland. Material and methods . The study included 162 questionnaires, which were filled in correctly by pregnant women (third trimester) who took part in childbirth classes organized by a childbirth school. As a research method, the PPAQ was chosen. The PPAQ allows pregnant women to self-assess their physical activity in the current trimester. The questions investigated time devoted to various types of activity related to household/caregiving, transportation, sports/exercise in their free time, occupational activity and inactivity. Based on the average weekly energy expenditure, each of these activities is classified by intensity: sedentary activity, light-intensity activity, moderate-intensity activity, vigorous-intensity activity. Results . While using the PPAQ in Poland, it is recommended to reduce the number of questions from 36 to 35, by removing question 18 (time of mowing lawn while on a riding mower). It is also advisable to convert American units of measurement into metric units, which are used in Poland. Conclusions . The Pregnancy Physical Activity Questionnaire in Poland may fill the gap in studies devoted to the physical activity of pregnant Polish women. With this questionnaire, it is possible to determine energy expenditure in terms of intensity and type of physical activity. It also serves as a reliable tool that can be used for international comparisons.